Theorising democide why and how democracies fail - Chou, Mark 1982- (Theories, concepts and practices of democracy, 2013)
The common assumption is that the path to democratisation is, once begun, near impossible to reverse. Particularly where democratic transition has been properly consolidated conventional wisdom and empirical evidence both suggest that no democracy should follow the example of Classical Athens or Germany's Weimar Republic and return to despotism. Starting from the premise that democracies are often deeply implicated in their own downfall, "Theorising Democide" challenges this conventional view by showing how democratic collapse is symptomatic of the inherent logic of democracy. Democide, in some cases, can thus be understood as a kind of ideological suicide with the tenets and devices of democracy being somehow intrinsic to its own collapse. In other words democide denotes the capacity that democracy has to come undone, to risk its own safety, to take its own life while doing what it was intended to do